AN OVERVIEW OF AIR POLLUTION AND ITS HEALTH EFFECTS ON URBAN SETTLEMENT: A NIGERIA’S PERSPECTIVES - A. ALIYU, ABUBAKAR; SA’IDU, HARUNA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Air pollution is one of the major causes of health problems confronting humans today. Presently, there is certainly a high rate of atmospheric pollution in Nigeria especially in the densely populated urban cities. Besides, pollution levels may be rising as a result of increased motor vehicle traffic building on already congested roads. Consequently, accumulation of these pollutants in the atmosphere in large quantities and of longer duration poses harm to human health. Ultimately, people living in urban and industrial areas are particularly prone to varied types of diseases due to air pollution. Prevalent diseases resulting from exposure to these pollutants include pertussis, pulmonary tuberculosis, cerebral spinal meningitis (CSM), pneumonia, measles, chronic bronchitis, and upper respiratory tract infection (URTI). This review therefore focus on the effects of primary air pollutants on human health with the objective of examining their various sources, chemical composition and emission of these pollutants comprising of Nitrogen oxides (NOx), Carbon monoxide (CO), Particulate material (PM), Sulphur dioxide (SO2), Volatile organic compounds (VOCs), and Lead (Pb). In view of these problems, control measures are likewise discussed. The human environment being the basis for any economic, social and cultural development needs to be maintained in a good state to ensure a high level of social performance. These can only be achieved through closer monitoring of the pollutants released by motor vehicles and industries, which can adequately help in reducing air pollution effects to the bearest minimum.